AWARENESS OF HAND, FOOT AND MOUTH DISEASE AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Hand, Foot and Mouth Disease (HFM) is often a potentially infectious condition primarily caused through enteroviruses. Clinical manifestations involve erythematous papules mostly on arms, legs, and even in the oral cavity, followed by prodromal effects such as myalgia, moderate fever, and abdominal distress. This survey was conducted to assess hand, foot, and mouth disease awareness among dental students. This was a questionnaire based cross sectional type of survey comprising 100 dental college students in Chennai. A self-designed questionnaire containing 10 queries based on the knowledge and awareness about Hand, Foot and mouth disease (HFMD) among dental college students. Questionnaires were distributed through an online website survey planet. After the responses were received from 100 participants, data was collected and analysed.47% are aware about HFMD. 34%are aware of the clinical manifestation of HFMD. 31%Are aware of the mode of transmission of HFMD. 26% are aware of the preventive measures against HFMD.18%.are aware of incubation period of HFMD. 24%aware of treatment measures for HFMD. This study found the dental students displayed less knowledge and understanding of HFMD. Even, there are few differences in knowledge and behaviors that require enhancement. Large-scale health awareness initiatives of HFMD should be implemented by professional associations in order to fill these gaps and improve awareness in order to positively impact their attitudes.